Structural materials: fire and protection - Findik, Fehim (Heritage and Sustainable Development, 2022)
Any material that can be used in the construction of a building is called building material. Concrete, reinforced concrete, steel, aluminum, wood, tile, plaster, etc., known as building materials. Fire is a chemical event that occurs as a result of the combination of matter with heat and oxygen. Fire protection is the study and practice of reducing the undesirable effects of destructive fires. It includes the behavior, suppression and investigation of fire. In this study, building materials such as steel, concrete and wood were examined, and then the protection of building materials using fire resistant materials and fire systems was emphasized.